Oral Steatocystoma Simplex—A Rare Tumor. Issue 5 (September 2021) - Bawazir, Maram; Lozano, Teresa; Cohen, Donald M.; Islam, Mohammed N.; Bhattacharyya, Indraneel
Abstract: Steatocystoma is a benign adnexal tumor that originates from sebaceous glands or ducts. Steatocystoma simplex presents as a solitary, noninherited tumor that affects adults with equal sex predilection. It can affect any part of the body and is seen most commonly on the skin of the face and neck. Involvement of the oral mucosa is extremely rare. To the best of our knowledge, only 3 intraoral cases have ever been reported. We report a rare case of steatocystoma simplex presented in a 17-year-old male patient involving the buccal mucosa.